RCP GAS FIELD DEVELOPMENT PLAN TO FULLFILL GAS SALES AGREEMENT PLAN - Herianto, Herianto; Kristianto, Dedi; Rahmawan, Dhimas Arief (Universitas Pembangunan Nasional Veteran Yogayakarta, 2022)
The RCP field is an exploration field which is currently in the early development stage. From the drilling of exploration wells, a gas reservoir has been found in the Basal Sand formation. The Basal Sand Formation itself is a fairly deep formation and includes a large reservoirhigh pressure high temperature(HPHT). This RCP field hasInitial Gas Inplace IGIP) of 1202 Bcf. Currently there is a demand for gas supply of 50 MMSCFD for 10 years, so it is necessary to evaluate as a supporter of the Gas Sale and Purchase Agreement (PJBG). This research is expected to find out that the RCP field is able to fulfill the PJBG according to the plan. The development of the RCP Gas Field starts from the IGIP calculation, then calculations are carried outrecovery factorto getestimate ultimate recovery(EUR), which will then be corrected for reserves of impurities. The next stage is the field development scheme. For field development during the PJBG contract period, it is planned to use 3 development wells with optimization of the production rate using chokes. Gross rate field of 67 MMSCFD (22.3 MMSCFD per well) to getgas salesof 50 MMSCFD. After planning the development of the field, the next step is to calculate the economy. The economic calculation is calculated using the PSC scheme based on Fiscal Termapplicable in the RCP field. The results of the analysis of the development scheme show that the RCP field is able to produce according to the PJBG plan with gas sales daily amount of 50 MMSCFD for 10 years. Economic calculations show positive results so that it is concluded that the RCP Field has economic value and is feasible to be developed. From the economic calculation, we get NPV@10 % = 96.2 MM US; IRR = 27.1%; POTS = 2.5 years.